COMPARATIVE STUDY TO ASSESS THE PLACENTAL WEIGHT AND FETAL OUTCOME IN NORMAL MOTHERS AND ANAEMIC MOTHERS DURING INTRANATAL PERIOD IN SELECTED HOSPITALS. - Lalhriatpuii, Bali Thool (International Journal of Modern Agriculture, 2020)
Introduction: The most common hematological condition that may occur during pregnancy is anemia. It is a decrease in the blood's oxygen carrying ability – a reduction in the number of red blood cells (RBC) or a low hemoglobin concentration. Objectives: - 1) To assess the placental weight in normal mothers and anaemic mothers. 2)To assess the foetal outcome in normal mothers and anaemic mothers. 3)To compare the placental weight and foetal outcome in normal and anaemic mothers. Methodology- It is an academic hospital-based study and it will be conducted among 60 mothers with normal and anaemic from AVBRH respectively. An observational checklist will be used to collect the data. Ethics approval was obtained from IEC, DMIMS (DMIMS(DU)/IEC/Dec - 2019/ 8638). The conclusion will be drawn from the results and will be published in peer reviewed journal. Expected Results: The study will enhance the knowledge regarding the need and importance of proper diet among the women especially during pregnancy. Findings will also improve the importance of MCH programme which are organized by the Government of India regarding the prevention of anaemia.